IMPLEMENTASI KEBIJAKAN PEMBERIAN BANTUAN OPERASIONAL SEKOLAH PADA SD INPRES PRULEME KABUPATEN PUNCAK JAYA - Kogoya, Longga; Ohoiwutun, Yosephina; Sapioper, Hiskia C.M. (JURNAL KEBIJAKAN PUBLIK, 2025)
This study aims to analyze the implementation of the School Operational Fund (BOS) policy at SD Inpres Pruleme, Puncak Jaya Regency. The focus of the study includes policy implementation, supporting and inhibiting factors, and the school's efforts to optimize the use of BOS funds. The research method used is qualitative with a descriptive approach. Data collection techniques include in-depth interviews, observations, and document studies. Research informants were determined using purposive sampling techniques. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of the BOS policy at SD Inpres Pruleme, from a communication perspective, is still constrained by suboptimal information dissemination and coordination. Furthermore, in terms of resources, there are limitations in human resources for financial management and inadequate infrastructure. In terms of disposition, although policy implementers demonstrate commitment in managing BOS funds, understanding of technical regulations and the participation of the school committee in oversight still need to be improved. From the bureaucratic structure aspect, the mechanism for disbursing and reporting BOS funds is still hampered by complex administrative procedures and the lack of an effective monitoring system. Supporting factors include community support, effective communication between schools and the Education Office, and transparency in financial reporting. Meanwhile, the inhibiting factors are limited infrastructure, low budget management capacity, miscommunication between governments, and difficult road access, which hinder distribution and the effectiveness of BOS fund use. Improvement efforts are carried out through transparent planning, capacity building through training, publication of financial reports, optimization of fund use according to priorities, and regular monitoring and evaluation to enhance education quality.